PEMAHAMAN HADIS KONSERVASI LINGKUNGAN DAN INTERNALISASINYA PADA CIVITAS AKADEMIKA PROGRAM STUDI ILMU HADIS IAIN KEDIRI - Umi Hanik; Ibnu Hajar Ansori; A Zahid (Asketik : Jurnal Agama dan Perubahan Sosial, 2021)
As part of the ecological system, humans have a dominant role in determining the good andbad of the environment. The stability and comfort of the environment depend on the positivebehavior around the elements of the ecosystem in it, including humans. The emergence of variousenvironmental problems is also inseparable from human indiscipline in protecting and preservingthem. An environment that is maintained properly, will respond positively by providing greatbenefits to humans. Otherwise, an environment that is treated badly will repay with damage anddisaster. The leadership of the Faculty of Ushuluddin and Da’wah at IAIN Kediri was fully aware ofthis, especially the Hadith Science Study Program. This awareness forms a religious constructionbased on an understanding of religious texts, particularly Hadith. Through qualitative research,this reality will be described descriptively and analytically. The results illustrate that the epitomeconstruction of environmental conservation activities is manifested in participation in the GreenCampus program. The sociological construction contestation was seen in the leadership of the HadithScience Study Program and the academic community for the absorption of religious teaching, thusgenerating practices in the form of involvement in tree and flower planting activities in the Facultyof Ushuluddin and Da’wah.